Lost in the funhouse: Allegorical horror and cognitive mapping in Jordan Peele's Us. Issue 1 (1st March 2021) - Booker, M. Keith; Daraiseh, Isra
Jordan Peele's Us (2019) is an entertaining horror film that also contains a number of interesting interpretive complications. The film is undoubtedly meant as a commentary on the inequity, inequality and injustice that saturate our supposedly egalitarian American society. Beyond that vague and general characterization, though, the film offers a number of interesting (and more specific) allegorical interpretations, none of which in themselves seem quite adequate. This article explores the plethora of signs that circulate through Us, demanding interpretation but defeating any definitive interpretation. This article explores the way Us offers clues to its meaning through engagement with the horror genre in general (especially the home invasion subgenre) and through dialogue with specific predecessors in the horror genre. At the same time, we investigate the rich array of other ways in which the film offers suggested political interpretations, none of which seem quite adequate. We then conclude, however, that such interpretive failures might well be a key message of the film, which demonstrates the difficulty of fully grasping the complex and difficult social problems of contemporary American society in a way that can be well described by Fredric Jameson's now classic vision of the general difficulty of cognitive mapping in the late capitalist world.